2013
DOI: 10.1177/0004563213483458
|View full text |Cite
|
Sign up to set email alerts
|

Maturity onset diabetes of the young: identification and diagnosis

Abstract: Maturity-onset diabetes of the young (MODY) is a monogenic disorder that results in a familial, young-onset non-insulin dependent form of diabetes, typically presenting in lean young adults before 25 years. Approximately 1% of diabetes has a monogenic cause but this is frequently misdiagnosed as Type 1 or Type 2 diabetes. A correct genetic diagnosis is important as it often leads to improved treatment for those affected with diabetes and enables predictive genetic testing for their asymptomatic relatives. An e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 111 publications
4
108
1
8
Order By: Relevance
“…Neither of the patients who had genetic variants in our cohort had unusual BMI. Patient 1 with the HNF4A mutation was lean (BMI SD –0.78), in keeping with previous reports of the phenotype associated with MODY 1 [34], but not exceptionally so, whilst Patient 2 with the HNF1B mutation had a normal BMI for age (BMI SD 0.22) at the time of study. In a study from Germany involving children and adults, anti-GAD positivity was detected in 22% of MODY cases [35].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Neither of the patients who had genetic variants in our cohort had unusual BMI. Patient 1 with the HNF4A mutation was lean (BMI SD –0.78), in keeping with previous reports of the phenotype associated with MODY 1 [34], but not exceptionally so, whilst Patient 2 with the HNF1B mutation had a normal BMI for age (BMI SD 0.22) at the time of study. In a study from Germany involving children and adults, anti-GAD positivity was detected in 22% of MODY cases [35].…”
Section: Discussionsupporting
confidence: 88%
“…One of the additional benefits of identifying patients with MODY is that insulin is ineffective in controlling their diabetes in some forms of MODY and an effective alternative treatment can be given. Although HNF1B (Patient 2) mutations still require insulin therapy, both HNF1A and HNF4A (Patient 1) are responsive, especially in the early stages of their diabetes, to treatment with sulfonylurea but may eventually require insulin therapy to be restarted [34]. It has been suggested that the replacement of multiple daily injections of insulin with therapy using sulfonylurea tablets may have the added benefit of increasing treatment adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Scores of genes have been causally implicated in monogenic forms of diabetes (e.g., neonatal diabetes mellitus [MIM: 601410] 73 ), but GWASs have now identified over 100 common variant signals. [74][75][76] Recent efforts to extend GWASs beyond arraybased genotyping and to access a broader range of variants through sequencing (particularly those of lower frequency) have revealed that most genetic variation influencing T2D appears to reside at common variant sites.…”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…In the liver, they regulate lipoprotein biosynthesis 22 . Mutations in these transcription factor genes result in an alteration of gene expression of proteins that are involved in glucose transport and glucose metabolism and increase apoptosis of the -cells 23 .…”
Section: Transcription Factor Genes Modymentioning
confidence: 99%